On the Lotka–Volterra competition system with Allee effects - Jang, Sophia R.-J. (Computational and Applied Mathematics, 2013)
We study asymptotic dynamics of the classical Lotka–Volterra competition model when both competing populations are subject to Allee effects. The resulting system can have up to four interior steady states. In such case, it is proved that both competing populations may either go extinct, coexist, or one population drives the other population to extinction depending on initial conditions.